Download presentation
Presentation is loading. Please wait.
1
Standard Gibbs Free Energy
Review Standard Gibbs Free Energy Go = Ho - TSo Go < 0 spontaneous Go = kJ/mol Go > 0 non-spontaneous Go = kJ/mol Go = 0 equilibrium Go = kJ/mol glucose + phosphate glucose-6-phosphate + H2O ATP + H2O ADP + phosphate glucose + ATP ADP + glucose-6-phosphate
2
Non-standard conditions
reaction quotient = [products] m Q = initial [reactants] n initial K = equilibrium constant = [products] m equilibrium [reactants] equilibrium n G = - RT ln ( ) K /Q K > Q G < 0 spontaneous G > 0 K < Q non-spontaneous K = Q G = 0 equilibrium
3
Go G = - RT ln(K) o G = - RT ln(K/Q) Standard Free Energy
Impose Standard conditions: [reactants]initial = 1(M or atm) = [products]initial Q = 1 G = - RT ln(K) o Standard Free Energy
4
Non-Standard Conditions
G = Go + RT ln Q G = - RT ln (K/Q) Go = - RT ln K ln (a/b) = ln a - ln b G = - RT ln (K/Q) = -RT ln K + RT ln Q
5
Go = - RT ln(K) G = - RT ln ( ) K /Q G < [products] glucose
+ phosphate glucose-6-phosphate + H2O standard conditions non-spontaneous Go = kJ/mol = -RT ln K K = 1.2 x 10-3 -RT G = - RT ln ( ) K /Q G < Q < K < 1.2 x 10-3 non-standard conditions [products] [reactants] initial Q = start with no product spontaneous
6
Non-Standard Conditions
G = Go + RT ln Q 2NO2 (g) N2O4 (g) Initially [NO2] = 0.3 M [N2O4] = 0.5 M Will more products or reactants be formed? Q = 0.5 / 0.32 = 5.6
7
Non-Standard Conditions
G = Go + RT ln Q 2NO2 (g) N2O4 (g) Initially [NO2] = 0.3 M [N2O4] = 0.5 M Gorxn = Gof products - Gof reactants = 2(51.3) = - 4.8 kJ/mol Grxn= -4.8 + (8.314 x 10-3)(298) ln 5.6 = -0.5 kJ/mol More N2O4 will be formed
8
Le Chatelier’s Principle
G = -RT ln (K/Q) A +B C K = [C]e Q = [C]i [A]e[B]e [A]i[B]i Le Chatelier’s Principle Add A decrease Q K/Q > 1 Add B G > < 0 Remove A increase Q K/Q < 1
9
Temperature dependence of K
exothermic reaction heat = product at low T favor forward reaction at high T favor reaction reverse endothermic reaction heat = reactant at low T favor reaction reverse at high T favor reaction forward
10
Temperature dependence of K
Go = -RT ln K Go = Ho - TSo -RT ln K = Ho - TSo - Ho R 1 T + So R ln K = m x b ln K y Ho < 0 1/T increase T decrease K T
11
Temperature dependence of K
Go = -RT ln K Go = Ho - TSo -RT ln K = Ho - TSo - Ho R 1 T ln K = + So R - ln K y m x b endothermic H > 0 1/T increase T increase K T
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.